Assessment of the competition level of junior female volleyball players - Nicolescu, I.; Rada, L. (Journal of Physical Education and Sport, 2017)
The preparation of female players is a planned, systematic and long-term process in which the objective is to obtain performance. During training, ongoing transformations occur both in terms of performance and in its structural components. These components presume progressive development and gradual stages that include complex functional, structural and psychological modifications, which are induced by the combination and variety that are required for competitions. A coach`s objective is to offer the sportsman with a possibility to permanently and efficiently use their functional potential during their competitive actions.